Multiple Input Multiple Output (MIMO) Model of an Industrial Ecosystem: An Agent-Based Modeling Approach - Ajisegiri, G. O.; Muller, F. L. (Engineering, Technology & Applied Science Research, 2020)
This paper addresses the application of the Agent-Based Model (ABM) to simulate the evolution of Multiple Input Multiple Output (MIMO) eco-industrial parks to gain insight into their behavior. ABM technique has proven to be an effective tool that can be used to express the evolution of eco-industrial parks. The ABM represents autonomous entities, each with dynamic behavior. The agents within the eco-industrial park are factories, market buyers, and market sellers. The results showed that the Réseau agent-based model allowed the investigation of the behaviors exhibited by different agents in exchange for materials in the industrial park.